Implementasi Model Problem Based Learning Berbantuan Media Augmented Reality Untuk Meningkatkan Sikap Gotong Royong dan Prestasi Belajar IPAS Kelas VI SD - Pambudi, Bekti Pri; Muslim, Arifin (Jurnal Ilmiah Global Education, 2025)
This study aims to improve the cooperative attitude and learning achievement of sixth-grade students at SD Negeri Sidaurip 03, particularly in the subject “Our Earth is Threatened by Danger.” To achieve this goal, the Problem-Based Learning Model was applied with the assistance of Augmented Reality media. This combination is expected to create a more interactive and engaging learning experience. This study employs the Classroom Action Research (CAR) method by Kemmis & McTaggart in two cycles, involving 14 students. Data was collected through observation, questionnaires, as well as pre-tests and post-tests, providing a comprehensive overview of the changes that occurred. The research results indicate a clear improvement in both aspects. Students' cooperative attitudes showed improved: from 58.04% (adequate category) in the pre-cycle, increasing to 73.32% (good category) in Cycle I, and reaching 81.25% (good category) in Cycle II. This improvement indicates that students are becoming more active in collaborating and supporting one another. Similarly, IPAS learning achievement also showed a strong increase. The average score increased from 56.79% in the pre-cycle with a completion rate of 14.28%. After implementing the Problem-Based Learning model and Augmented Reality media, the average score rose to 64.61% in Cycle I with a completion rate of 57.14%, and finally reached 81.07% in Cycle II with a completion rate of 92,86% (excellent category). This data proves that the combination of the Problem-Based Learning model and Augmented Reality media is highly effective in enhancing students' understanding and academic achievements. This study concludes that the implementation of the Problem-Based Learning model and Augmented Reality media has a strong positive impact on improving students' cooperative attitudes and IPAS academic performance.